Peningkatan Hasil Belajar Biologi dengan Penerapan Model Jigsaw - Mumtaza, Puspita Zakiya; Selaras, Ganda Hijrah (Lembaga Yasin AlSys, 2023)
The use of learning models such as a jigsaw with a helpful methodology is one of the methods to further develop biology learning outcomes. In Jigsaw learning, students give opinions to each other and are required to help each other. The motivation behind doing this research is to find out how far the Jigsaw model further develops biology learning outcomes. Literature review or literature study is the research method used in this research. It can be proven from the findings of articles and journals that the Jigsaw model can increase student activity, learning outcomes, and collaboration between students.